Sustainable Urban Development in the European Arctic - Wehrmann, Dorothea; Łuszczuk, Michał; Radzik-Maruszak, Katarzyna; Götze, Jacqueline; Riedel, Arne (Taylor & Francis, 2025)
Focusing on cities in the European Arctic, this book consolidates research on sustainable development, local and urban governance, and transnational cooperation in the region. It examines to what extent there is transnational cooperation between urban areas in remote locations and how it can be enhanced to better align with global sustainable development policies to successfully implement goals such as the 2030 Agenda for Sustainable Development and the Paris Climate Agreement. Based on field research in seven cities in the European Arctic, Rovaniemi, Kolari, Nuuk, Akureyri, Tromsø, Kiruna, and Luleå, the authors explain why approaches to sustainable urban development differ between geographies, how policies relate to other local and global strategies, and to what degree the European Arctic is normative for remote regions at large. This book contributes to important conceptual debates on local governance and transnational cooperation by examining the benefits and potential issues of applying theoretical models of multi-actor engagement and participation in isolated populations. It argues that the participation of local actors in decision processes may encourage a better harmonisation of sustainable urban development approaches in the European Arctic and will have a greater impact at the global level if aligned transnationally. This book will be relevant to researchers, social scientists, policymakers, practitioners, and NGOs in the fields of global governance, sustainable development, sustainability research, and environmental studies. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.